Investigating the Impact of the Social Media Branding on Purchase Intention in the African Context - Burle, Peter Nyara Bashir; Wang, Ning; Zhu, Anding (International Journal of Economics, Business and Management Studies, 2022)
Start-ups play an important role in providing job opportunities and promoting economic development. Social media enables start-ups to reach customers at a more affordable cost than traditional channels. The present study aims to explore the possibility of using social media for African start-ups as a marketing and branding tool and to investigate the effects of social media branding on African consumers’ purchase behaviours. Multiple studies were conducted. First, two case studies of African start-ups were made to obtain feasible business models of social media branding. Then, a qualitative pilot study was conducted to explore the consensus map of social media branding from the consumers’ perspective. Finally, a model was established and verified by employing a quantitative approach. Six constructs of trust, interaction, social support, information sharing, brand relationship, and brand engagement are identified. Among them, trust plays a crucial role in the context of African markets. By using SEM testing, the present study reveals that brand relationship and brand engagement act as mediators between social media branding factors and consumers’ purchase intentions. In Africa, the idea of branding via social media is appealing for start-ups due to the emergence and growth of various social media platforms. The present study provides an overall view of social media branding for African start-ups, including business models, consumer engagement, and consumer experience. The insights and suggestions will be beneficial for African start-ups and will contribute to the African business literature.